ANALISIS PENDAPATAN PETANI KARET ANGGOTA KUB DI DESA PULAU RAMBAI KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - Shintya Wulandari; Shorea Khaswarina; Eliza Eliza (Fakultas Pertanian, Universitas Riau, 2021)
Rubber farmers of KUB members are rubber farmers who are members of KUB, farmers who are involved in the marketing of rubber produced to be sold directly to the factory through KUB so that farmers get high prices and affect the income received by farmers. The purpose of this study is to analyze the income and efficiency of KUB rubber farmers farming in Rambai Island Village, Kampar Timur Sub-District with the consideration that Desa Rambai Village has the highest production in Kampar Timur Sub-District. Data used in this research are primary data and secondary data. The analysis used is income analysis of rubber farmers by calculating production cost, gross income and net income and farm efficiency analysis. The results showed that the net income of rubber farmers of KUB members was Rp 21.142.903,24 /ha/year with total production cost of Rp 17.569.832,96 /ha/year. The value of farming efficiency or RCR of rubber farmers members of KUB > 1 is 2,20 means that farming by KUB rubber farmers in Desa Rambai is efficient and feasible to be developed.